Analysis of translation strategies in the change of meaning in The Fairy Tale Les Souhaits Ridicules - Asmarani Irawan, Hana; Amalia, Farida; Mulyadi, Yadi (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This study investigates the semantic translation strategies employed in the meaning shifts of Charles Perrault’s fairy tale Les Souhaits Ridicules, translated into Indonesian. Utilizing a qualitative approach and Chesterman’s 1997 translation strategy theory, the research identified and classified semantic techniques including synonymy, paraphrasing, antonymy, converses, emphasis, distribution, and hyponymy shifts. Analysis of 92 data points conclusively revealed  that paraphrasing (43.48%) and synonymy (27.17%) were the most prevalent strategies, with emphasis shifts also significantly present (17.39%). These findings indicate that meaning shifts are executed functionally and adaptively, aiming to preserve acceptability and readability for young Indonesian readers without compromising the story’s moral message or narrative essence. By comparing these results with prior studies, this research offers a substantial contribution to the exploration of semantic strategies in children’s literature translation, underscoring the importance of translator flexibility and cultural sensitivity. The study’s limitations, particularly its scope and singular focus on semantic strategies, provide clear directions for future research into cross-linguistic and cross-cultural translation within the fairy tale genre.